The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/pl00006507
|View full text |Cite
|
Sign up to set email alerts
|

N-Carbamoyl Amino Acid Solid–Gas Nitrosation by NO/NO x : A New Route to Oligopeptides via α-Amino Acid N-Carboxyanhydride. Prebiotic Implications

Abstract: Alpha-N-Carbamoyl amino acid (CAA), whose conditions of formation in a prebiotic hydrosphere have been described previously (Taillades et al. 1998), could have been an important intermediate in prebiotic peptide synthesis through reaction with atmospheric NOx. Nitrosation of solid CAA (glycine or valine derivative) by a 4/1 NO/O2 gaseous mixture (1 atm) yields N-carboxyanhydride (NCA) quantitatively in less than 1 h at room temperature. The crude solid NCA undergoes quantitative oligomerization (from trimer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…N-Carbamoyl amino acids have been shown to be very interesting precursors of Ncarboxyanhydrides [52] [53]. N-Phosphoryl a-amino acids lead to oligopeptides via a five-membered cyclic pentacoordinate phosphoric-carboxylic mixed anhydrides resembling the N-carboxyanhydrides [54].…”
mentioning
confidence: 99%
“…N-Carbamoyl amino acids have been shown to be very interesting precursors of Ncarboxyanhydrides [52] [53]. N-Phosphoryl a-amino acids lead to oligopeptides via a five-membered cyclic pentacoordinate phosphoric-carboxylic mixed anhydrides resembling the N-carboxyanhydrides [54].…”
mentioning
confidence: 99%
“…Condensation of N-carboxy anhydrides (NCA), conversely, begins to be accepted as a prebiotic method of chain formation [10], and, in fact, the group of Commeyras has approached the very problem of the prebiotic formation of sequential peptides by this method [10 -12] (see also Blocher et al [13]). However, also in this case, the critical question of the production of multiple identical copies of long (30 or more) cooligopeptides could not yet be achieved.…”
mentioning
confidence: 99%
“…Synthesis: The synthesis of the first generation of polyA C H T U N G T R E N N U N G (llysine) was carried out by a three-step sequence (Scheme 2) by implementing the knowledge from our research group [17,28,29] and by starting from N-carbamoyl derivative CLysA C H T U N G T R E N N U N G (Tfa), which was prepared by a straightforward NcarbamA C H T U N G T R E N N U N G oylation of N e -trifluoroacetyl-l-lysine. [29] NO + O 2 -promoted nitrosation [28] of C-LysA C H T U N G T R E N N U N G (Tfa) in acetonitrile gave monomer LysA C H T U N G T R E N N U N G (Tfa)-NCA, which was then reacted in aqueous sodium hydrogen carbonate (pH 6.5) to give N e -protected oligoA C H T U N G T R E N N U N G (l-lysine) G1P.…”
Section: Resultsmentioning
confidence: 99%
“…[15] As an example based on peptide bonds, Klok et al [14,16] reported the synthesis of dendritic graft polyA C H T U N G T R E N N U N G (l-lysine)s by iterative co-polycondensation of two differently N e -protected amino acid N-carboxyanhydrides (NCA) in dimethylformamide, followed by the selective removal of one of these sets of protecting groups; a final, complete deprotection step then afforded the desired dendritic graft polyA C H T U N G T R E N N U N G (llysine). [14] Our recent investigations on NCA chemistry in water (in connection with their possible key role in the emergence of life through the prebiotic chemistry of peptides), [17][18][19] gave us the opportunity to address the synthesis of lysine arborescent polymer in an original manner. Because of their high Abstract in French: Nous dØcrivons la synthse et la caractØ-risation de nouvelles architectures arborescentes de polyA C H T U N G T R E N N U N G (llysine), nommØes dendrimres greffØs de lysine (DGL).…”
Section: Introductionmentioning
confidence: 99%